Risk Factors for Totally Implantable Access Ports Associated Complications in Breast Cancer Patients - Yangfan Fan MD; Xiaohang Ye MD; Fangfang Chen MD; Fang Wan MD; Dianlei Liu MD; Tao Zhang MD, PhD; Jingpei Long MD (Cancer Control)
Objective To investigate the risk factors for complications in breast cancer patients with totally implantable access ports (TIAPs). Methods This retrospective case-control study involved 471 breast cancer (BC) patients who received TIAPs during chemotherapy. We compared the demographic and clinical characteristics of patients with complications to those without, analyzed independent risk factors using binary logistic regression, and identified differences in complication rates based on catheterization site. Results The most frequent complication was catheter malposition, followed by infection, thrombosis, hemothorax, and port rotation. Complications were more common in right-side BC cases ( P = .026) and with left-side insertions ( P = .012). Binary logistic regression identified independent risk factors for complications: catheter tip location (OR = 0.599, P = .013), and catheterization site (OR = 0.319, P = .019). Notably, left-side insertion significantly increased the risk of overall complications and catheter malposition compared to right-side insertion (OR = 3.534, P = .008; OR = 5.624, P = .004, respectively). Conclusion Catheter tip location and catheterization site independently affect complications and catheter malposition. For TIAPs implantation, particularly on the left side, a lower catheter tip location is advised to reduce complications and enhance safety.